Per‐6‐Thiol‐Cyclodextrin Engineered [FeFe]‐Hydrogenase Mimic/CdSe Quantum Dot Assembly for Photocatalytic Hydrogen Production. Issue 2 (14th October 2020) - Li, Xu-Bing; Jian, Jing-Xin; Wang, Xu-Zhe; Wang, Yang; Xia, Shu-Guang; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : [FeFe]‐hydrogenase ([FeFe]‐H2 ase) mimics, inspired by hydrogenases in nature, have emerged as an important class of molecular catalysts toward hydrogen (H2 ) evolution. Herein, a per‐6‐thiol‐cyclodextrin (CDSH) engineered [FeFe]‐H2 ase mimic/CdSe quantum dot (QD) assembly is established for effective photocatalytic H2 evolution. In the assembly, CDSH is first anchored on CdSe QDs via the strong multidentate Cd‐thiol coordination. Then, [FeFe]‐H2 ase mimic is assembled on the QD surface via the host–guest supramolecular interaction between the hydrophobic cavity of cyclodextrin (CD) and the adamantyl (AD) group of [FeFe]‐H2 ase mimic. In neutral aqueous solution of isopropanol, the Fe2 S2 ‐AD/CDSH/CdSe assembly exhibits a turnover number (TON) of 1.12 × 10 5 (based on Fe2 S2 ‐AD) under visible light, which is about 12‐fold to the corresponding system without CDSH. Mechanistic insights indicate that the CDSH can not only prevent the aggregation of QDs in acidic conditions, but also balance the interfacial charge (electron and hole) transfer to avoid the photocorrosion of QDs, thereby giving the highest TON of H2 photogeneration based on [FeFe]‐H2 ase mimics up to date. Abstract : Herein, a per‐6‐thiol‐cyclodextrin (CDSH) engineered [FeFe]‐hydrogenase ([FeFe]‐H2 ase) mimic/CdSe quantum dot (QD) assembly is established for effective photocatalytic hydrogen (H2 ) evolution under solar light. Due to the enhanced stability of QDs in aqueous solution and the balanced interfacial electron and hole transfer, the highest turnover number (TON) of H2 photogeneration (1.12 × 10 5 ) based on [FeFe]‐H2 ase mimic is achieved.